Profile of Students' Conceptual Understanding of the Pythagorean Theorem Viewed from Learning Styles - Yulta Sobe Pagallaran; Bakri Mallo; Mustamin Idris; Fajriani Fajriani (FKIP - Universitas Riau, 2026)
Conceptual understanding of mathematics enables individuals to explore and comprehend mathematical concepts. However, many students face obstacles in mastering these concepts due to various internal and external factors. This study aims to describe the profile of students' conceptual understanding of the Pythagorean Theorem in Grade VIII of SMP Negeri 1 Sigi viewed from learning styles. This research employed a descriptive qualitative approach. Data were collected through a learning style questionnaire, written tests, and interviews, and analyzed using the Miles and Huberman model with time triangulation to ensure data credibility. The results show that all three subjects PA (visual), IM (auditory), and COM (kinesthetic) met all three conceptual understanding indicators: restating a concept, presenting a concept in mathematical representation, and using and selecting certain operational procedures. However, differences were found in their thinking process characteristics: the visual subject demonstrated strong visual-spatial reasoning; the auditory subject showed structured verbal reasoning; and the kinesthetic subject applied systematic step-by-step procedures guided by contextual cues. It is concluded that learning style influences not only learning outcomes but also the characteristics of students' conceptual understanding profiles.